Pemanfaatan Sistem Informasi Spasial untuk Pengelolaan Aset di Desa Bligo Kecamatan Candi Kabupaten Sidoarjo - Moch. Shofwan; Anak Agung Sagung Alit Widyastuty; Linda Dwi Rohmadiani; Suning Suning; Siti Nuurlaily Rukmana; Annisa Budhiyani Tribhuwaneswari (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
Bligo Village is a village located in Candi District, Sidoarjo Regency. Utilization of the village spatial information system is highly expected for the realization of village asset data collection that is able to support the Bligo Village Government which is good governance and competitive. The purpose of this study is to provide training on Village Spatial Information Systems for Village Asset Management. The method used is divided into two stages of data collection, namely primary data collection consisting of observation and documentation. Subsequent data collection is carried out on a secondary basis by being obliged to fill in the data that has been distributed into the questionnaire. As a result, it is known that the SWOT value in this analysis is located in quadrant I, meaning that it is able to improve the quality of human resources in village officials regarding the use of spatial information systems for asset management in Bligo Village, Candi District, Sidoarjo Regency.